1990
DOI: 10.1002/jbm.820241003
|View full text |Cite
|
Sign up to set email alerts
|

The bone–titanium interfacein vitro

Abstract: Commercially pure 5-mm-diameter titanium (cpTi) discs received droplet inoculations of cells derived from rat bone marrow and were maintained in supplemented culture medium for 2-3 weeks. The cells and extracellular matrix (ECM) were processed for observation by light (LM), scanning (SEM), and transmission electron (TEM) microscopy. The latter was achieved by freeze-fracturing the solid metal from the resin-embedded tissue using a method which preserved the interface. Surface staining of whole discs revealed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(85 citation statements)
references
References 14 publications
2
79
0
3
Order By: Relevance
“…Generally it is not believed that there is a direct chemical bond between titanium and bone tissue, but when the term osseointegration was coined by Brhnemark in the 1970s, a chemical bond may have been implied. Later, ultrastructural studies indicated an amorphous ground substance at the bone-implant interface, which appeared not to support the idea of a chemical bond , Linder 1989a, b, Davies et al 1990). Osseointegration then became defined as contact between implant and bone without an intervening fibrous tissue layer at the interface, on the light microscopic level (Carlsson et al 1986).…”
mentioning
confidence: 93%
“…Generally it is not believed that there is a direct chemical bond between titanium and bone tissue, but when the term osseointegration was coined by Brhnemark in the 1970s, a chemical bond may have been implied. Later, ultrastructural studies indicated an amorphous ground substance at the bone-implant interface, which appeared not to support the idea of a chemical bond , Linder 1989a, b, Davies et al 1990). Osseointegration then became defined as contact between implant and bone without an intervening fibrous tissue layer at the interface, on the light microscopic level (Carlsson et al 1986).…”
mentioning
confidence: 93%
“…This layering has been confirmed by previous studies, showing crystals of HA beneath the cells. 5,8 The inner stratum of Ca on the Ti surface has been described previously after analysis of the bone-implant interface of healed-in implants by atom probe tomography. 19 This analytical method can only detect basic elements and does not provide molecular information.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the bone-titanium implant border has remained an object of continuous study during four decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, studies of the established material/bone interface cannot give definite answers to the time-dependence of the subprocesses of bone formation. The only possible way to obtain this information is to make time-lapse studies of bone healing at implants.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts derived from rat bone marrow stroma were isolated from the femurs of young adult male Wistar rats weighing approximately 120 g (Japan Clea Co., Ltd., Tokyo, Japan), according to the method of Maniatopoulos et al 15,16 For the primary culture, both femora were removed and washed 4 times in α -minimal essential medium containing antibiotic solution (1.0 mg/mL penicillin G, 0.5 mg/mL gentamicin, and 3.0 μg/mL amphotericin B). The epiphyses were then cut from both femora, and the marrow cells were flushed out with 30 mL of α -minimal essential medium supplemented with 15% fetal bovine serum, 10 mM β -glycerophosphate, 10 −8 M dexamethasone, 50 μ g/mL ascorbic acid, and antibiotics at one tenth of the concentrations listed above.…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…In the culture system used in this study, 15,16 mesenchymal stem cells were included in the rat bone marrow stroma isolated from the femora. Mesenchymal stem cells differentiate into osteogenic cells, and osteoprogenitor cells differentiate into osteoblasts.…”
mentioning
confidence: 99%